La ferme de Seumay à Perwez (suite) - Debras, Louis; Wilmet, Jules (Le Souvenir Perwézien, 2000)
Keywords: seumay

La ferme de Seumay à Perwez (suite) - Debras, Louis; Wilmet, Jules (Le Souvenir Perwézien, 2000)
Keywords: seumay

La ferme de Seumay à Perwez (suite) - Debras, Louis; Wilmet, Jules (Le Souvenir Perwézien, 2000)
Keywords: seumay

La ferme de Seumay à Perwez - Debras, Louis; Wilmet, Jules (Le Souvenir Perwézien, 2000)
Keywords: seumay

Le chartrier de l'abbaye prémontrée de Saint-Yved de Braine (1134-1250) - Guyotjeannin, Olivier (École des Chartes, 2000)
Keywords: braine

Thierry de Tuldel et les Prémontrés brabançons face à la commende (1470-1481) - Appelmans, Janick (Analecta Praemonstratensia, 2000)
During the later middle ages holding an abbey in commendam meant that is was granted to a secular clergyman, for example a bishop, a dean or a secular canon. At Saint Michael's abbey in Antwerp as well as in Tongerlo these commendators were influential members of the Burgundian court and high-ranking ecclesiastical officials. These princes of the church gave the duke more control over his clergymen and were in return provided with a substantially increased income. Ferry de Clugny made at Tongerlo in the years 1470-1471 the first successful intrusion in a Premonstratensian monastery in Brabant. His aspirations could be bought off by a lifelong rent. Diederik van Tuldel (1419-1494), the abbot of Park since 1462, undertook different diplomatic initiatives at the papal court in order to safeguard the Brabantine abbeys from more commendators. Despite many apostolic letters and guarantees his efforts were vain. In 1477 two bishops were appointed as the heads of the communities of Antwerp and Tongerlo. The reign of the commendatory prelates started at an ill fated moment, just a few weeks after the death of Duke Charles the Bold. The central government was not able any longer to support firmly the commendators in their struggle to obtain their offices and revenues. In contrast to the many collations of Benedictine abbeys in commendam the princes of the church faced well-informed and organized opponents. At several times the different Brabantine abbots gathered to discuss the state of affairs and took action against the commendators. Diederik van Tuldel and his fellow prelates knew every move of the secular abbots and their supporters. Therefore the abbot of Park could rely upon a network of trustful informers and skilled negotiators, including abbots and Premonstratensian delegates as well as merchants and church officials at the papal court. The last commendator finally resigned in 1481, but it had necessitated many funds to compel the secular abbots to desist from their prerogatives. Since his journey to Rome in 1475 Diederik van Tuldel had co-ordinated the defense of the liberties and rights of Saint Norbert's order and had taken care of the financial settlements. With the repetitive, but sometimes reluctant, consent of the order's general chapter the taille, a taxation within the order, was used. It lasted almost fifteen years before all the debts were reimbursed.
Keywords: park; 🇧🇪 belgium (general)

Quelques chapiteaux romans et gothiques de l'ancienne abbaye de la Case-Dieu - Balagna, Christophe (Actes de la 21e journée des archéologues gersois, Vic-Fezensac, 1999, 2000)
Keywords: case dieu

Approches archéologiques de l’abbaye prémontrée Notre-Dame de Val-Secret - Blary, François (Utilis est lapis in structura : mélanges offerts à Léon Pressouyre, 2000)
Keywords: val-secret

Bibliothèques de l'Ordre de Prémontré dans la France d'Ancien Régime: Répertoire des abbayes - Bondéelle-Souchier, Anne (CNRS Éditions, 2000)
Keywords: 🇫🇷 france (general)

L'architecture prémontrée dans l'Espagne médiévale: recherches et premiers bilans - Dauzet, Dominique-Marie (Analecta Praemonstratensia, 2000)
Keywords: 🇪🇸 spain (general)

L'habitat à Caen aux XIVe et XVe siècle: l'exemple des propriétés de l'abbaye d'Ardenne dans le quartier Saint-Sauveur – rue Ecuyère - Delente, Robert (Annales de Normandie: Revue semestrielle d'études régionales, 2000)
Keywords: ardenne

Les sceaux de l'abbaye de La Lucerne - Ducoeur, Danièle (Revue de l'Avranchin et du pays de Granville, 2000)
Keywords: la lucerne

Recherches sur Vanault-les-Dames et Vanault-le-Châtel du 10e au 13e siècle - Hirschmann, Frank G. (Vivre au village en Champagne à travers les siècles, 2000)
Keywords: vanault-les-dames

L'Abbaye de Licques: 1070-1224 - Ramecourt, Isabelle (Université du Littoral Côte d'Opale, 2000)
Keywords: licques